Prognostic impact of tumor-specific insulin-like growth factor binding protein 7 (IGFBP7) levels in breast cancer: a prospective cohort study. (4th October 2021) - Godina, Christopher; Khazaei, Somayeh; Tryggvadottir, Helga; Visse, Edward; Nodin, Björn; Jirström, Karin; Borgquist, Signe; Bosch, Ana; Isaksson, Karolin; Jernström, Helena
Abstract: The prognostic impact of insulin-like growth factor binding protein 7 (IGFBP7) in breast cancer is unclear. Host factors, including lifestyle, anthropometry and metabolic profile, might influence tumor-specific IGFBP7. This study aimed to investigate whether IGFBP7 levels and messenger ribonucleic acid (mRNA) expression are associated with the patient and tumor characteristics and prognosis in breast cancer. Patients with primary breast cancer in Lund, Sweden, were included preoperatively in the study between 2002 and 2012 ( n = 1018). Tumor-specific IGFBP7 protein levels were evaluated with immunohistochemistry using tissue microarrays in tumors from 878 patients. IGFBP7 mRNA expression and its corresponding clinical data were obtained from The Cancer Genome Atlas and analyzed for 809 patients. Tumor-specific IGFBP7 protein levels were categorized based on Histo 300 scores into IGFBP7 low (6.2%), IGFBP7 intermediate (75.7%) and IGFBP7 high (18.1%). Both low IGFBP7 protein levels and mRNA expression were associated with less aggressive tumor characteristics. Overall, IGFBP7 low conferred low recurrence risk. The prognostic impact of IGFBP7 high varied according to any alcohol consumption and tamoxifen treatment. IGFBP7 high was associated with low recurrence risk in alcohol consumers but high recurrence risk in alcohol abstainers ( P interaction = 0.039). Moreover, the combination of IGFBP7 high and estrogen receptor-positive tumors was associated with low recurrence risk only in tamoxifen-treated patients ( P interaction = 0.029). To conclude, IGFBP7 low might be a good, independent prognosticator in breast cancer. The prognostic impact of IGFBP7 high depends on host factors and treatment. IGFBP7 merits further investigation to confirm whether it could be a suitable biomarker for treatment selection. Abstract : We investigated the prognostic impact of tumor-specific IGFBP7 levels in breast cancer. Overall, low IGFBP7 conferred good prognosis, while high IGFBP7 in ER + tumors conferred good prognosis in tamoxifen-treated patients. IGFBP7 merits further investigation as a biomarker for treatment selection. Graphical Abstract: